Top‐down control of plant communities by consumers - Jiang, Hongying; Ke, Junsheng; Zhang, Peng; Dang, Yilin; Liu, Xiang (The Journal of ecology, 2025)
Trophic interactions are widely recognized to be a fundamental force shaping plant populations and communities. However, our understanding of how different consumers (i.e. grazers, insect herbivores and pathogens) affect plant performance (i.e. biomass, diversity, reproduction and/or survival) is fragmentary, particularly across diverse ecosystems and environmental contexts. We conducted a global meta‐analysis of 3135 data comparisons from 296 papers to quantify the effects of removing plant consumers on plant biomass, diversity, reproduction and survival. We examined how these effects varied across ecosystem types (forest or grassland), levels of ecological organization (population or community) and study designs (field or pot experiment), as well as along environmental gradients (e.g. of temperature and precipitation) and across spatial scales (i.e. different plot sizes). Pathogen removal increased plant survival but reduced plant species diversity, supporting a role for pathogens in maintaining diversity through conspecific negative density dependence (CNDD). The removal of insect herbivores enhanced plant biomass, reproduction and survival, particularly at the population level and in field experiments. Grazing exclusion increased plant biomass, reproduction and survival, with legumes and trees showing particularly strong responses. The effects of pathogen removal on survival and grazing exclusion on biomass and reproduction were moderated by plot area, with stronger effects observed in larger plots. Synthesis. Our findings highlight the critical role of trophic interactions in shaping plant communities through top‐down regulation. Grazers, insect herbivores and pathogens differentially impacted plant performance, with pathogens playing a key role in maintaining plant diversity through CNDD, while herbivores and grazers strongly regulated plant biomass, reproduction and survival. Our results also underscore the importance of considering spatial scale and environmental context when assessing consumer effects on plant communities. Ongoing global change may amplify these effects, with significant implications for plant community structure and biodiversity conservation. 中文摘要 营养级相互作用通常被认为是塑造植物种群和群落的重要力量。然而，我们对不同消费者(即牧食动物、植食性昆虫和病原体)如何影响植物性能(如生物量、多样性、繁殖和/或存活)的理解仍不全面，尤其是在不同生态系统类型中和不同环境背景下。 我们收集了296篇文献中的3,135组数据对，进行开展了一项全球尺度的荟萃分析，量化了移除植物消费者对植物生物量、多样性、繁殖和存活的影响。我们进一步探究了这些效应如何随生态系统类型(森林或草地)、生物组织水平(种群或群落)、研究设计(田间或盆栽实验)、环境梯度(如温度和降水)及空间尺度(即不同样方面积)而变化。 病原体移除提高了植物存活率但降低了物种多样性，这支持了病原体通过同种负密度依赖(CNDD)维持多样性的作用。植食性昆虫的移除增强了植物生物量、繁殖力和存活率，上述效应尤其在种群水平和田间实验中更为显著。排除放牧则增加了植物生物量、繁殖力和存活率，其中豆科植物和乔木响应尤为强烈。病原体移除对存活的影响以及放牧排除对生物量和繁殖的影响均受样方面积调控，即更大样方中观测到的效应更强。 总结:我们的研究揭示了营养级相互作用通过自上而下的调控塑造植物群落。牧食动物、植食性昆虫和病原体对植物性能的影响存在差异:病原体通过CNDD在维持植物多样性中发挥核心作用，而牧食动物和植食性昆虫则强烈地调控植物生物量、繁殖与存活。研究结果同时强调了评估消费者效应时需要着重考虑空间尺度和环境背景。持续的全球变化可能放大上述效应，这些发现对植物群落结构维持和生物多样性保护具有深远意义。 Our global meta‐analysis reveals differential impacts of consumer removal: Pathogen exclusion ↑ survival but ↓ diversity (via CNDD); insect herbivore removal ↑ biomass/reproduction/survival; grazer exclusion ↑ biomass/reproduction/survival (strong in legumes/trees); effects amplified in larger plots, demonstrating scale‐dependent top‐down control of plant communities.